Ultrafast Förster resonance energy transfer between tyrosine and tryptophan: potential contributions to protein–water dynamics measurements. Issue 30 (21st July 2022) - Li, Haoyang; Jiang, Guanyu; Jia, Menghui; Cao, Simin; Zhang, Sanjun; Chen, Jinquan; Sun, Haitao; Xu, Jianhua; Knutson, Jay R.
Abstract : Schematic diagram of ultrafast energy transfer from tyrosine to tryptophan in model peptides (WY, WPY, WP2Y, WP3Y). With the increase of peptide chain length, the lifetime of energy transfer first decreases and then increases. Abstract : Ultrafast Förster Resonance Energy Transfer (FRET) between Tyrosine (Tyr, Y) and Tryptophan (Trp, W) in the model peptides Trp-(Pro) n -Tyr (WP n Y) has been investigated using a femtosecond up-conversion spectrophotofluorometer. The ultrafast energy transfer process (<100 ps) in short peptides (WY, WPY and WP2Y) has been resolved. In fact, this FRET rate is found to be mixed with the rates of solvent relaxation (SR), ultrafast population decay (QSSQ) and other lifetime components. To further dissect and analyze the FRET, a spectral working model is constructed, and the contribution of a FRET lifetime is separated by reconciling the shapes of decay associated spectra (DAS). Surprisingly, FRET efficiency did not decrease monotonically with the growth of the peptide chain (as expected) but increased first and then decreased. The highest FRET efficiency occurred in peptide WPY. The kinetic results have been accompanied with molecular dynamics simulations that reconcile and explain this strange phenomenon: due to the strong interaction between amino acids, the distance between the donor and receptor in peptide WPY is actually closest, resulting in the fastest FRET. In addition, the FRET lifetimes ( τ cal ) were estimated within the molecular dynamics simulations, and they were consistent with the lifetimes ( τ exp ) separated out by the experimental measurements and the DAS working model. This benchmark study has implications for both previous and future studies of protein ultrafast dynamics. The approach taken can be generalized for the study of proximate tyrosine and tryptophan in proteins and it suggests spectral strategies for extracting mixed rates in other complex FRET problems.